Aproveitamento do resíduo líquido industrial do sisal (Agave sisalana Perr.) para obtenção de um inseticida biológico - Costa, Milena Ferreira (2012)
The low utilization of the leaves of Agave sisalana, around 4%, motivated this research which aims to assess the effects of compounds from the secondary metabolism of this species in the development and survival of the fall armyworm, in corn. For this purpose were used essentially eight treatments: ethanolic extract at concentrations of 1,25; 2,5; 5,0; 7,5 and 10%, butanolic extract to 1,5 and 3,0%, ethyl acetate extract to 1,0 and 2,0%, and three control treatments: synthetic insecticide Lannate, distilled water and insecticide Nim-I-Go. Samples of residue were analyzed by colorimetric tests and precipitation to verify the chemical composition. In the biological assays was assessed the duration of life stages larval and pupal, the weight, mortality, length and width of body of the larvae, in tests by topical application and ingestion. Scales were used to assess both the damage of phytotoxicity of the extracts as the damage of the fall armyworm in the field, including the production of culture. It was observed the presence of triterpenoids, saponins and tannins in the samples. The plant extracts showed toxicity foliar damage comparable to commercial insecticides, and similarly in the field, where the infestation was controlled as from the 2nd application, without interfering in the production of culture. The extracts act most strongly by ingestion and affect the survival of the larvae, with emphasis on acetate to 2,0% and ethanolic to 10%, with 100% mortality and action in the first days of life of the insect.